2018
DOI: 10.1111/bor.12311
|View full text |Cite
|
Sign up to set email alerts
|

Stratigraphical signatures of glacier activity, marine processes and a possible tsunami in the Leirfjorden fjord‐valley system, north Norway

Abstract: An integrated interpretation of on‐ and offshore stratigraphical records at Leirfjorden, north Norway, reveals new aspects of the area's palaeoenvironmental history. The study is based on marine sparker data and well‐exposed sections on land that were analysed for their sediment facies, mineralogy and fossil assemblages. Existing research and new radiocarbon dates provide a chronological framework for the interpretation. The late Younger Dryas Nordli substage type locality in the Leirfjorden catchment is revis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Although the time of onset of erosion is unknown, in the depressions along the foot of the Stjernsundet Moraine and along the southern margin of Stjernsundet, erosion appears to be an ongoing process. Similar erosional features along steep slopes (at the seabed and buried in the stratigraphy) have been observed in many Norwegian fjords (e.g., Bøe et al, 2003;Hansen et al, 2018) and are interpreted to be related to changes in fjord circulation following changes in glacier positions/meltwater discharge, river discharge, and tidal and oceanographic circulation.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Although the time of onset of erosion is unknown, in the depressions along the foot of the Stjernsundet Moraine and along the southern margin of Stjernsundet, erosion appears to be an ongoing process. Similar erosional features along steep slopes (at the seabed and buried in the stratigraphy) have been observed in many Norwegian fjords (e.g., Bøe et al, 2003;Hansen et al, 2018) and are interpreted to be related to changes in fjord circulation following changes in glacier positions/meltwater discharge, river discharge, and tidal and oceanographic circulation.…”
Section: Discussionsupporting
confidence: 66%
“…Unit D and underlying strata onlap the Stjernsundet Moraine and are assumed to be of glacimarine origin. Similar, alternating units of stratified and homogeneous sediments occur above glacial deposits in most Norwegian fjords (e.g., Bøe et al, 2003Bøe et al, , 2004bHansen et al, 2018) where their accumulated thickness may reach hundreds of metres. The hummocky appearance and varying thickness of Unit C suggests that this is a mass movement deposit.…”
Section: Sedimentary Processes and Depositional Environments -Stjernsundetmentioning
confidence: 82%
“…1; Andersen et al, 1982). Marginal moraines related to the event have been traced onshore (Andersen et al, 1981;Hansen et al, 2018), whilst large submarine icemarginal deposits have been identified and mapped in the outer parts of the fjords (Andersen et al, 1982;Lyså et al, 2004). Bargel (2003) mapped end moraines and ice-marginal features in the outer Tosenfjord region (Fig.…”
Section: Introductionmentioning
confidence: 99%